Uma Proposta de Análise de Algoritmos de Machine Learning para o Envio e Recebimento de Notificações em Ambientes Inteligentes - A. Martins, João; O. Rolim, Carlos; R.Q. Leithardt, Valderi (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2019: Anais da XIX Escola Regional de Alto Desempenho da Região Sul, 2019)
The objective of this proposal is to present steps for the development of future work, which will perform an analysis of supervised machine learning algorithms of classification task, which will address classification accuracy in sending and receiving notifications in environments intelligent, based on the control and privacy management middleware, called UBIPRI.